2022
DOI: 10.3390/e24111667
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Benefit Analysis of Grain Trade in Belt and Road Countries

Abstract: Grain trade in Belt and Road (B&R) countries shows a mismatch between the volume and direction of grain flows and actual demand. With economic and industrial development, the water crisis has intensified, which poses a great challenge to the security of world grain supply and demand. There are few studies on the reconstruction of grain trade relations from the perspective of grain economic value. In this paper, a linear optimization model considering opportunity cost is proposed to fill the gap, and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Regarding China's grain trade, China's food security issue has always been a focus of studies, with its food consumption and imports ranking among the highest levels globally, making it the largest food consumer country in the world. Du (2022) [16] found that grain trade in the Belt and Road region shows a mismatch between the direction of grain trade flows and actual demand. Ukraine and Russia are the largest grain exporters in the Belt and Road region, and China should seize the opportunity to strengthen cooperation.…”
Section: Related Research 121 Research On Agricultural Product Trade ...mentioning
confidence: 99%
“…Regarding China's grain trade, China's food security issue has always been a focus of studies, with its food consumption and imports ranking among the highest levels globally, making it the largest food consumer country in the world. Du (2022) [16] found that grain trade in the Belt and Road region shows a mismatch between the direction of grain trade flows and actual demand. Ukraine and Russia are the largest grain exporters in the Belt and Road region, and China should seize the opportunity to strengthen cooperation.…”
Section: Related Research 121 Research On Agricultural Product Trade ...mentioning
confidence: 99%
“…In the face of issues such as imbalanced grain supply and demand with the restricted trade and transportation, China's government has ensured national food security by increasing grain yields [14][15][16], safeguarding food consumption [17], expanding grain storage [18][19][20], and enhancing grain trade [21,22]. As a basis for national stability [23,24], this yield is positively influenced by various underlying driving factors, such as farmland quality [25,26], agricultural mechanization input [27,28], fertilizer and pesticide use [29,30], agricultural subsidies [31,32], and urbanization [33,34].…”
Section: Introductionmentioning
confidence: 99%